REGULATORY FOCUS DAN EMPLOYEE WELL BEING PADA DOSEN PERGURUAN TINGGI NEGERI - Haznah, Siti Amira; Rahmi, Tuti; Febriani, Utari (Causalita, 2024)
The purpose of this study was to determine the contribution of the regulatory focus on employee well-being at state university lecturers. Regulatory focus consists of prevention focus and promotion focus which are considered variables in research because they are multidimensional constructs. This research uses a quantitative approach with a survey method. The data collection technique was carried out by cluster sampling. The subjects of this study were lecturers at state universities in Indonesia with a total of 98 respondents. Data analysis used multiple linear regression analysis with SPSS 20 for windows. The hypothesis results show that the prevention focus variable partially contributes to employee wellbeing with P (0.000 <0.05). The promotion focus variable partially has no contribution to employee wellbeing with P (0.480 > 0.05). Meanwhile, prevention focus and promotion focus simultaneously contributed to employee wellbeing with P (0.001<0.05). The result of the R square value shows 0.150. This means that the prevention and promotion variables simultaneously contribute to the employee well-being variable by 15.0%. While the remaining 85.0% is influenced by other variables outside the research.